Direct-drive implosion physics: Results from OMEGA and the National Ignition Facility. (March 2016) - Radha, P. B.; Goncharov, V. N.; Hohenberger, M.; Sangster, T. C.; Betti, R.; Craxton, R. S.; Edgell, D. H.; Epstein, R.; Froula, D. H.; Marozas, J. A.; Marshall, F. J.; McCrory, R. L.; et al.
Abstract: Direct-drive-implosion experiments from both OMEGA and the National Ignition Facility (NIF) are critical to gain confidence in ignition predictions on the NIF. Adequate performance of hydrodynamically scaled 1.8-MJ ignition designs must be obtained on OMEGA at 26 kJ. Implosions on the NIF must be used to identify and mitigate the effect of laser-plasma interactions (LPI's) on hydrodynamic parameters at the NIF scale. Results from spherically driven OMEGA cryogenic implosion experiments are described. Mitigation of nonuniformity sources and cross-beam energy transfer (CBET) is important for improving target performance on OMEGA. Initial polar-driven implosion experiments on the NIF have provided valuable measurements of trajectory and symmetry. Simulations that include the effect of CBET more closely reproduce the observed velocity.